Road Safety in Puglia Region - Bonerba, Pierpaolo (TeMA - Journal of Land Use, Mobility and Environment, 2009)
The increasing amount of traffic on the Italian road system and the number of road accidents has put the attention of the road safety problem at European, National and Regional levels. The Italian Govern with the National Plan of Road Safety (PNSS 1999) defined the strategies for road safety and to reduce road accidents. The Puglia Region with the Regional Law 18/2004 instituted the Centre for Monitoring Road Safety (CReMSS), whose issue is to collect data about road incidents and accidents, to define potential risks and to improve road infrastructure. The CReMSS has defined an integrated monitoring centre for road safety and accident prevention, and constitute a central resource and information management centre. The main Puglia Region strategy on road safety is roads safer for everyone and the key targets is to reduce the number of people killed or seriously injured in road accidents. The Cremss publishes reports on road safety issues and detailed statistics on Puglia Region road traffic. CReMSS is also involved in road safety publicity campaign and surveys that monitor attitudes to key road safety issues. The present situation in Puglia region demonstrates an allarming situation as from 2006 the number of accidents has not reduced, and from the 2000 the number of accidents almost duplicates (from 5.883 in 2000 to 11.776 in 2007); the number of people killed went from 374 to 366 and the number of people injured from 9.866 to 19.652. For this reason the role of CReMSS is central and really important. The general objective that Puglia Region took has been the implementation of a monitoring centre to analyse and prevent road accidents with a specific target of the RegionalTerritory. The overall strategy underlying the actions undertaken by the Puglia Region is, as a main goal, the building of a new road safety culture to solicit attendance from the local authority, the region, other bodies dealing with the road network, schools and citizen association towards a safer and sustainable mobility. In addition, the enhancement of technical structures in charge of traffic and safety has been achieved. The expected results concern: – improvement of cooperation between all actors involved; – improvement of a local integrated culture about road safety; – availability of a powerful analysis tool and a Monitoring Centre; – development of some operational plans to improve safety and reduce crashes risks in the most critical points. – report progress in implementing the road safety strategy directed at reducing the number of accidents and casualties; – report the effectiveness of casualty reduction measures. – report on progress with road safety partnerships.